Multimodal Project-Based Learning Through Transmediation:Design for Arabic Literature Learning - Ilham, Andri; Nafi’ah, Khotimatun; Mutmainah, Mia; Sarip, Mohamad; Jubaidah, Siti; Binta, Silmi Malina (Universitas Negeri Semarang, 2025)
In order to assist students in comprehending and analyzing literary works more thoroughly, learning Arabic literature calls for a creative method. Through transmediation, this study seeks to create a multimodal project-based learning model that uses a variety of media to improve students' understanding and creativity. This research employs the Research and Development (R&D) method, following the Hannafin and Peck model, which consists of three phases: need assessment, design, and development & implementation. However, this study focuses only on the need assessment and design phases. Data were collected through observations and questionnaires distributed to students and lecturers in the Arabic Literature course of the Arabic Language Education Study Program at Universitas Negeri Jakarta. The needs assessment results indicate that students face difficulties in deeply understanding Arabic literary texts and are less actively engaged in the learning process. To improve their understanding of Arabic literature, a more project-based and interactive approach is required. Based on these results, the design phase produced a multimodal project-based learning model integrating transmediation, enabling students to express their understanding through visual, audio, and digital storytelling. In order to determine how the created model affects students' critical thinking, creativity, and understanding of Arabic literature, this study suggests that it be further implemented and evaluated. The usefulness and efficacy of this learning model should be investigated further during the development and implementation phases.